Examining Teaching Reading Using Local Culture-Based Pictorial Narrative Texts: A Case Study to Secondary School Students - Fauzi, Iwan; Asi, Natalina; Saman, Tampung N.; Karani, Elanneri; Luardini, Maria Arina; Ngabut, Mary Novary (Jurnal Pendidikan Edutama, 2024)
The local culture integration in foreign language (FL) reading classroom can help learners understanding text more easily and quickly. This research took 37 secondary school students in the junior level (11 males & 26 females) as the sample. The quantitative research method was used with a case-study research design. There were three research objectives focused in this study: (1) the influence of local culture-based pictorial narrative texts on students' reading comprehension; (2) the correlation between students' perceptions of integrating local culture into the development of reading materials and students' reading comprehension; and (3) the difference of problems faced by students in understanding pictorial narrative texts in terms of purpose of the story, characters in the story, orientation, complications, and resolution of the story. The results showed that local culture-based pictorial narratives had a significant effect on students' reading comprehension, and were positively correlated to each other. In addition, students do not have discrepancy in terms of problems encountered when understanding the narratives such as the purpose of the story, characters in the story, orientation, complication, and resolution of the story.